China’s Historical Relations with West Africa, 1960-65: An Analysis of Ideology, Economic Aid, and Foreign Policy Practices - Jin, Yuan (International Journal of Social Sciences and Public Administration, 2025)
This paper examines China's foreign relations with West Africa during the period from 1960 to 1965, focusing on the ideological, economic, and diplomatic strategies employed by China to strengthen its influence in the region. During a time of global Cold War tensions and the Sino-Soviet split, China sought to form alliances with newly independent African nations such as Ghana, Mali, and Guinea. By promoting anti-imperialist and socialist ideologies, China positioned itself as a supporter of national liberation movements in Africa. The paper analyzes the role of economic aid as a tool for political leverage, examining specific aid projects that fostered economic development in these countries while aligning them ideologically with China. The study also explores the diplomatic interactions between Chinese and African leaders, emphasizing how these relationships were instrumental in gaining support for China on the international stage, particularly in the United Nations. The research provides insights into the broader implications of China's early foreign policy strategies in the Third World and its long-lasting impact on Sino-African relations.